2008
DOI: 10.1111/j.1468-1293.2008.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow‐up in an international, multicentre observational study

Abstract: ObjectiveThe aim of this work was to assess loss to follow-up (LTFU) in EuroSIDA, an international multicentre observational cohort study. MethodsLTFU was defined as no follow-up visit, CD4 cell count measurement or viral load measurement after 1 January 2006. Poisson regression was used to describe factors related to LTFU. ResultsThe incidence of LTFU in 12 304 patients was 3.72 per 100 person-years of follow-up [95% confidence interval (CI) 3.58-3.86; 2712 LTFU] and varied among countries from 0.67 to 13.35.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
81
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 18 publications
16
81
4
2
Order By: Relevance
“…Our overall rate of one in five becoming lost to UK follow up (after exclusion of deaths) was higher than the 8.5% [21] and 11.9% [23] from two cohorts in France, but was comparable to the 25% reported by an Italian cohort with a high proportion of injecting drug users [26], the 27% reported by a Boston clinical cohort [22], the 22.0% reported by EuroSIDA (a clinical cohort encompassing 93 clinical centres in Europe, Israel and Argentina [24]), and the 16% reported in a survey of community-based settings led by the American Foundation of AIDS Research [25]. These differences were not explained by significant variations in definitions of LFU, as the majority defined LFU as patients who had not been seen in a clinic for at least 12 months [22-24,26-28].…”
Section: Discussionmentioning
confidence: 69%
“…Our overall rate of one in five becoming lost to UK follow up (after exclusion of deaths) was higher than the 8.5% [21] and 11.9% [23] from two cohorts in France, but was comparable to the 25% reported by an Italian cohort with a high proportion of injecting drug users [26], the 27% reported by a Boston clinical cohort [22], the 22.0% reported by EuroSIDA (a clinical cohort encompassing 93 clinical centres in Europe, Israel and Argentina [24]), and the 16% reported in a survey of community-based settings led by the American Foundation of AIDS Research [25]. These differences were not explained by significant variations in definitions of LFU, as the majority defined LFU as patients who had not been seen in a clinic for at least 12 months [22-24,26-28].…”
Section: Discussionmentioning
confidence: 69%
“…Estos 210.000 individuos con carga viral indetec- El programa de HIV/sida del Hospital Universitario San Ignacio presentó una tasa de densidad de la incidencia de la pérdida en el seguimiento de 17,74 por 100 personas por año, mucho más alta que la observada en otros estudios (3,72; 5,1 y 9,1 por 100 personas por año) (18)(19)(20), aunque en otras poblaciones se han descrito tasas de pérdida en el seguimiento superiores a lo reportado en este estudio (25,1 y 21,4 por 100 personas por año) (21,22). Las diferencias entre los estudios podrían deberse a las diversas metodologías aplicadas, así como a diferencias en la definición de pérdida en el seguimiento, en los tiempos de seguimiento de los estudios, en las poblaciones infectadas con HIV estudiadas y en las estructuras médicas locales (18,20).…”
Section: Discussionunclassified
“…Las diferencias entre los estudios podrían deberse a las diversas metodologías aplicadas, así como a diferencias en la definición de pérdida en el seguimiento, en los tiempos de seguimiento de los estudios, en las poblaciones infectadas con HIV estudiadas y en las estructuras médicas locales (18,20).…”
Section: Discussionunclassified
“…Although health service provision and populations of PLWH vary from country to country, these studies suggest that PLWH are less likely to disengage from care if they are male, 8 older, 8,21,28,29 white 8,22 and men who have sex with men (MSM) 22,23 and have started ART. 8,21 Socioeconomic factors and education have been highlighted in relation to disparities in EIC 30,31 and complex patient groups, such as intravenous drug users, migrants and the newly diagnosed, are more likely to disengage from care. 23 Although recent diagnosis is associated with poor retention in care, 8 there is also an indication that EIC can diminish over time.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…Researchers have assessed retention in care in a number of different ways. [21][22][23][24][25] These measures have their own strengths and weaknesses, 26 but none of them takes into account the fact that frequency of attendance is related to changes in treatment and health status and may also be affected by external forces or changes in clinic policy. In the UK, for example, guidelines at the time the REACH study was conducted indicated that patients should be seen within 2-4 weeks of starting ART and every 3-6 months for routine monitoring on ART if they were considered 'stable', with good adherence and an undetectable viral load.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%